2018
DOI: 10.1111/sms.13247
|View full text |Cite
|
Sign up to set email alerts
|

Population density and proximity to junior developmental teams affect the development of National Hockey League draftees

Abstract: Inconsistencies in community size effects found between and within countries (Baker et al Eur J Sport Sci. 2009;9:329-339; Bruner et al J Sports Sci. 2011;29:1337-1344; Wattie et al J Sports Sci. 2018;36:436-444) suggest population size may not be an accurate predictor of athlete development and that other proxies of early environmental characteristics are needed. Researchers have begun to explore the influence of population density and proximity to local sport clubs on athlete development in European countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While less densely populated communities may offer greater opportunities for free play and organized participation during the earlier stages of athlete development, the benefits of this environmental context may diminish if these communities are not populated enough to provide the necessary resources for higher levels of training and skill development (e.g., sport facilities, coaches and competitors; Curtis and Birch, 1987;Côté et al, 2006). More specifically, this deviation in participation trends across the developmental years could suggest different advantages associated with different environmental contexts at different timepoints; possibly reconciling the current findings with Farah et al (2018). This hypothesis is worthy of further investigation in future studies.…”
Section: Community Densitymentioning
confidence: 65%
See 3 more Smart Citations
“…While less densely populated communities may offer greater opportunities for free play and organized participation during the earlier stages of athlete development, the benefits of this environmental context may diminish if these communities are not populated enough to provide the necessary resources for higher levels of training and skill development (e.g., sport facilities, coaches and competitors; Curtis and Birch, 1987;Côté et al, 2006). More specifically, this deviation in participation trends across the developmental years could suggest different advantages associated with different environmental contexts at different timepoints; possibly reconciling the current findings with Farah et al (2018). This hypothesis is worthy of further investigation in future studies.…”
Section: Community Densitymentioning
confidence: 65%
“…However, inherent differences in the sport system, geography, population distribution, and other potentially relevant factors make comparisons difficult between North American and European contexts. Specific to the Canadian context, Farah et al (2018) reported an increased likelihood of being drafted into the National Hockey League for athletes from communities with higher population densities; but, the focus of the current study was on participation and continued engagement vs. athlete achievement.…”
Section: Community Densitymentioning
confidence: 91%
See 2 more Smart Citations
“…Danish research has shown that the presence or proximity of talent development clubs has a positive effect on the number of young players reaching elite status in both handball and football (Rossing et al, 2016(Rossing et al, , 2018. On the other hand, Farah et al (2018) did not find a positive effect of the proximity of an elite club on the chances of Canadian players reaching the NHL.…”
Section: Introductionmentioning
confidence: 88%